2005
DOI: 10.1056/nejmsa052596
|View full text |Cite
|
Sign up to set email alerts
|

Disciplinary Action by Medical Boards and Prior Behavior in Medical School

Abstract: In this case-control study, disciplinary action among practicing physicians by medical boards was strongly associated with unprofessional behavior in medical school. Students with the strongest association were those who were described as irresponsible or as having diminished ability to improve their behavior. Professionalism should have a central role in medical academics and throughout one's medical career.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
443
1
19

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 739 publications
(470 citation statements)
references
References 23 publications
7
443
1
19
Order By: Relevance
“…Risks highlighted in previous literature are based on unprofessional patient-physician contact [12] along with f "tweets" and "posts." Our presession surveys show that many residents witness unprofessional online content as reported in previous literature as well [4,13,14]. After the reflective approach session, residents stated they had improved their awareness in protecting patient privacy on digital media and would take a more proactive approach in ensuring professional use of social media and that they may modify their activity when using digital media both professionally and personally.…”
Section: Discussionsupporting
confidence: 63%
“…Risks highlighted in previous literature are based on unprofessional patient-physician contact [12] along with f "tweets" and "posts." Our presession surveys show that many residents witness unprofessional online content as reported in previous literature as well [4,13,14]. After the reflective approach session, residents stated they had improved their awareness in protecting patient privacy on digital media and would take a more proactive approach in ensuring professional use of social media and that they may modify their activity when using digital media both professionally and personally.…”
Section: Discussionsupporting
confidence: 63%
“…Papadakis et al then identified the specific types of inappropriate behaviour in medical school that were most predictive of disciplinary action against practicing physicians with unprofessional behaviour. 6 Disciplinary action by a medical board was strongly associated with evidence of severe irresponsibility and severely diminished capacity for selfimprovement. Disciplinary action by a medical board was also associated with low scores on the Medical College Admission Test and poor grades in the first two years of medical school, but the association with these variables was less strong than that with unprofessional behaviour while in medical school.…”
Section: Predicting Problem Patterns Of Behaviour In Physiciansmentioning
confidence: 99%
“…Qualitative information may be more sensitive for detecting individuals likely to exhibit poor professionalism. [10][11][12] Future works will examine the qualitative information from the PGY-1 Program Director surveys.…”
Section: Limitationsmentioning
confidence: 99%